2020
DOI: 10.3389/fphys.2020.01094
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Exogenous Ketone Monoester Ingestion on Plasma BDNF During an Oral Glucose Tolerance Test

Abstract: Brain-derived neurotrophic factor (BDNF) is important for brain and metabolic function. Ingestion of a ketone monoester (KME) drink containing beta-hydroxybutyrate (β-OHB) attenuates hyperglycemia in humans and increases neuronal BDNF in rodents. Whether KME affects BDNF in humans is currently unknown. This study examined the effect of KME ingestion before an oral glucose tolerance test (OGTT) on plasma BDNF in normalweight adults (NW) and adults with obesity (OB). Methods: Exploratory, secondary analyses of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…Improvements in cognitive function with β-OHB may be facilitated by BDNF (Arentoft et al 2009;Erickson et al 2012;Sun et al 2018). Animal and in vitro models show that β-OHB upregulates BDNF in neurons (Sleiman et al 2016;Marosi et al 2016;Hu et al 2018) and we have shown that β-OHB ingestion (0.45 mL kg -1 body weight; 3.4 mm peak) prior to an oral-glucose tolerance test (OGTT) increases plasma BDNF in adults with obesity (Walsh et al 2020). Accordingly, exogenous β-OHB supplementation may be a viable strategy for increasing BDNF and potentially proffering some neuroprotective effects, especially in vulnerable individuals.…”
Section: Introductionmentioning
confidence: 71%
See 3 more Smart Citations
“…Improvements in cognitive function with β-OHB may be facilitated by BDNF (Arentoft et al 2009;Erickson et al 2012;Sun et al 2018). Animal and in vitro models show that β-OHB upregulates BDNF in neurons (Sleiman et al 2016;Marosi et al 2016;Hu et al 2018) and we have shown that β-OHB ingestion (0.45 mL kg -1 body weight; 3.4 mm peak) prior to an oral-glucose tolerance test (OGTT) increases plasma BDNF in adults with obesity (Walsh et al 2020). Accordingly, exogenous β-OHB supplementation may be a viable strategy for increasing BDNF and potentially proffering some neuroprotective effects, especially in vulnerable individuals.…”
Section: Introductionmentioning
confidence: 71%
“…By contrast to our hypothesis, there was no effect on either plasma or serum BDNF. BDNF is lower in adults with obesity compared to normal weight adults (Krabbe et al 2007;Walsh et al 2020), which may have implications for cognitive dysfunction (Alosco & Gunstad, 2014;Prickett et al 2018;Sun et al 2018). Recently, we reported that acute β-OHB ingestion prior to an OGTT increases plasma BDNF 2 h following the consumption of a glucose load of 75 g in adults with obesity (Walsh et al 2020); however, the combination of β-OHB with OGTT precludes any inferences regarding the direct effect of β-OHB on BDNF.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…BDNF is one of the most wellstudied neurotrophins and is essential for brain function (Lima Giacobbo et al, 2019). Previous exploratory studies in human adults have found some associations between BHB and serum BDNF within a ketogenic diet intervention (Mohorko et al, 2019), and between BHB and plasma BDNF in the context of exogenous ketone ingestion (Walsh et al, 2020). Whether intake of kMCT, and subsequent ketosis, is associated with altered BDNF levels has to our knowledge not been studied.…”
Section: Introductionmentioning
confidence: 99%